PL.30 Fathers' Experiences of Pregnancy, Labour and Delivery. (26th April 2013) - McHugh, A; Hehir, MP; Balla, K; Foley, M; Mahony, R
Abstract : A fathers presence during labour is now commonplace in modern obstetric practise. We sought to evaluate fathers' experiences of pregnancy, labour and delivery. A survey was distributed to fathers in the postnatal period, and comprised of 17 questions. The questions were quantitative and multiple-choice in nature. No qualitative data was sought. A total of 1000 completed questionnaires were submitted for analysis. The mean age of fathers in the study was 33.8 years. Approximately 70% of the population were married, while 27.3% were in long term relationships. A significant percentage of the fathers were employed (88.1%) in paid work. Less than 8% were unemployed. First time fathers constituted the largest group (53.7%). Planned pregnancies constituted 77.9% with 2.5% as a result of fertility treatment. Seventy percent of fathers were 'overjoyed', 18.4% were 'pleased' and 11.3% responded either neutrally or negatively to the news of the pregnancy. Fathers were found to be likely to be present at ultrasound scans (89.1%) but less likely to be involved in antenatal education classes (48%). Almost all fathers were present at the delivery (97.2%). Nearly half of the fathers (49.6%) planned to attend the delivery because they really wanted to witness the birth, 43% attended to support their partner. At every stage of the pregnancy fathers perceived midwifery staff to have communicated better when compared to medical staff. Our quantitative survey found that in general fathers involvement with the pregnancy process and their attendance at the birth to be a positive experience. Communication processes can be improved to better support the father in his role during this time.